Pariwisata Berbasis Ekonomi Kreatif di Junrejo Kota Batu - ; Agustiawan Djoko Baruno (Syntax Idea)
This research aims to analyze and document the role of the creative economy in the development of the tourism sector in Junrejo, Batu City. The research was conducted using a qualitative approach, collecting data through in-depth interviews, field observations, and document studies. The research results indicate that the creative economy has become a major driver of tourism development in Junrejo. Various initiatives and collaborative efforts have enabled the emergence of unique and creatively oriented tourism products, services, and attractions. Additionally, this research also identifies factors that support the development of the creative economy in tourism, such as local community participation, local government support, and the availability of infrastructure. However, some challenges are also identified, such as the need to enhance the capacity of creative economic actors and promote sustainability in business practices. The findings of this research can provide guidance and insights for tourism stakeholders and local governments in designing policies that support the development of creative economy-based tourism in Junrejo, Batu City, and stimulate further research in this field.